2017
DOI: 10.1002/dmrr.2957
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 4 inhibitors attenuates the decline of skeletal muscle mass in patients with type 2 diabetes

Abstract: Our data suggest the potential of DPP4i to prevent the progressive loss of muscle mass with ageing in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 40 publications
1
31
3
Order By: Relevance
“…As a consequence, muscle mass and muscle function improved in Dex-induced muscle atrophy mice. In support of our results, recent studies reported that the inhibitors of DPP4, a GLP-1 degradation enzyme, are associated with improvement of reduced muscle mass in diabetic and elderly diabetic patients 15,71 and with improvement of mitochondrial biogenesis in a heart failure mouse model. 16 CKD is a model of cachexia that is mainly induced by inflammatory cytokines in the human pathological state.…”
Section: Discussionsupporting
confidence: 91%
“…As a consequence, muscle mass and muscle function improved in Dex-induced muscle atrophy mice. In support of our results, recent studies reported that the inhibitors of DPP4, a GLP-1 degradation enzyme, are associated with improvement of reduced muscle mass in diabetic and elderly diabetic patients 15,71 and with improvement of mitochondrial biogenesis in a heart failure mouse model. 16 CKD is a model of cachexia that is mainly induced by inflammatory cytokines in the human pathological state.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, it was reported that skeletal muscle indices were positively correlated with C-peptide, which showed endogenous insulin reserve [ 53 ], and dipeptidyl peptidase 4 inhibitors attenuated the decline of skeletal muscle in patients with T2DM [ 54 ]. Taken together, the present results demonstrated the importance of evaluating muscle quality in type 2 diabetic patients with visceral fat accumulation for potential risk assessment for atherosclerosis, suggesting that physicians might be better to consider selection of anti-diabetic agent from view point of the effect on skeletal muscle and support for patients in modifying their exercise habit.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DPP4 was shown to impair insulin signalling in smooth muscle cells, and its levels were increased in obese subjects causing insulin resistance 45,46 . Moreover, DPP4 inhibitors used in diabetes 2 treatment of elderly patients were demonstrated to prevent sarcopenia 47,48 . In this case, insulin insensitivity causes muscle loss.…”
Section: Discussionmentioning
confidence: 99%